2007
DOI: 10.1521/aeap.2007.19.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Theory–Based Predictors of Condom Use among University Students in the United States and South Africa

Abstract: This study compared the predictive value of the theory of planned behavior in university students in South Africa (N = 251) and the United States (N = 160) who completed an anonymous self-administered questionnaire. Multiple regression analyses revealed that condom use and intention were significantly predicted by positive condom attitude, subjective norm, self-efficacy, and attending university in South Africa. Significant interactions between country and predictors indicated that subjective norm predicted co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 16 publications
8
58
0
3
Order By: Relevance
“…This finding is consistent with previous studies on the relationship between self-efficacy and condom use (e.g., Heeren et al, 2007;Sheeran et al, 1999). Self-efficacy is also found to be a predictor of assertive sexual communication and communication about condom use among the heterosexual migrant sampels and a predictor of all three aspects of sexual communication among the homosexual sample.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with previous studies on the relationship between self-efficacy and condom use (e.g., Heeren et al, 2007;Sheeran et al, 1999). Self-efficacy is also found to be a predictor of assertive sexual communication and communication about condom use among the heterosexual migrant sampels and a predictor of all three aspects of sexual communication among the homosexual sample.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies identified the self-efficacy variable as an important associate of safe sex intentions and behavior Hendrickx et al, 2008;Heeren et al, 2007). In addition to the majority of previous research, which noted condom efficacy as a good predictor of intention to practice safe sex, the current study revealed that efficacy on limiting partners and abstinence are also good predictors of practicing safe sex.…”
Section: Discussionsupporting
confidence: 61%
“…34,51,52 Remember, however, that our application has considered only stages 1 and 2 of the ARRM, and the potential impact of interventions derived from these results relies on an assumption that intentions (and their facilitators such as self-efficacy) are related to actual behavior change as has been supported by several studies, 14,17,[59][60][61][62][63][64] but not as yet among heterosexual MA users. The significance of peer norms in directly or indirectly predicting intentions to change HIV risk behaviors in this population emphasizes the need for strategies to help build facilitating support structures to establish new or modified social networks and for the potential impact of wider social interventions designed to change general attitudes/norms for risk reduction.…”
Section: Implications For Addictions Health Servicesmentioning
confidence: 93%
“…61 Conner et al found that self-efficacy (one of the commitment facilitators) was a predictor of subsequent condom use behavior among offenders in substance abuse treatment. 14 Other examples supporting a relationship (direct or indirect) of self-efficacy with subsequent behavior change include Heeren et al, 62 Naar-King et al, 63 Robertson et al, 64 and Sanderson and Yopyk. 61 The treatment milieu is an optimal setting for the efficacious and cost efficient delivery of HIV prevention protocols targeting sexual and injection risk behavior among MA users.…”
Section: Aids Risk Reduction Model (Arrm)mentioning
confidence: 99%